Christian identity, Jews, and Israel in seventeenth-century England - Guibbory, Achsah, 1945- (Oxford University Press, 2010)
This book is a cultural history of 17th-century England. It explores the many, often contradictory ways people thought about themselves in relation to Jews, Judaism, & Jewish history. Grounded in archival research, the book analyzes the works of major writers including Foxe, Herbert, Bunyan, Milton, & Dryden.